Sosialisasi Promosi Wisata Alam Green View Danau Singkarak pada Media Sosial - Guswandi, Dodi; Hafizh, M.; Novita, Triana (Jurnal Pengabdian Masyarakat Dharma Andalas, 2024)
Green View Lake Singkarak is one of the tourist attractions located in Solok regency, West Sumatra with a breathtaking and interesting view with view of the mountains and Lake Singkarak that stretches widely, the number of tourists who visit this place is still small due to the lack of information spread on social media (Sosmed) such as Youtube, Instagram, Facebook, and Tiktok. So far, the dissemination of information about the beauty of this tourist attraction has only come from tourists who have visited this place. This community service was carried out by the Lecturer Team of Universitas Putra Indonesia YPTK Padang to increase the number of visitors to this tourist attraction so that people with a sales business and lodging around Green View Lake Singkarak can increase their income. After conducting socialization and training for the community who participate as participants in this service, they can use social media well by making content videos and other information about the natural beauty of Green View Lake Singkarak.